Poderes probatórios do juiz no processo coletivo - Daleprane, Cristina Passos (2012)
This study analyses the evidentiary powers of the judge in collective demands. It studies the evidentiary powers in general, highlighting the doctrinal and jurisprudential position. It also takes into account the fact that there are scholars who oppose the granting of broad powers to magistrates and in practice few operators of Law are taking evidentiary initiatives. This work examines the institution of proof from the constitutional approach and establishes the link between proof, process and truth. It reveals the utmost relevance of the contemporary Civil Procedure Science. It urges the strengthening of the evidentiary powers of the judge in group rights, with a view to social and political relevance of these actions. It demonstrates the importance of the procedural principles and Audi alteram partem as a mechanism to limit the authoritarianism of the magistrate. Moreover, in light of the cooperative principle, it asserts that the evidentiary activity is duty of the parties and the judge, as a result of the dialectical process. It also corroborates that the rational legal decision, accepted by the community for emanating the discourse in adversarial, has an intrinsic relationship with the efficient evidentiary instruction. It discusses the Model Code of Collective Procedure that appeared to inspire the creation of a single statute to govern group rights. It highlights the powers of acting and conducting given to the magistrate in the different phases of the collective process. For example, at the preliminary hearing, the distribution of the evidential burden, in the formation of res judicata secundum eventum probationis and management of the civil inquiry, before its use as evidence outside the record.